2014
DOI: 10.1038/ncomms4220
|View full text |Cite
|
Sign up to set email alerts
|

X-ray refinement significantly underestimates the level of microscopic heterogeneity in biomolecular crystals

Abstract: Biomolecular X-ray structures typically provide a static, time- and ensemble-averaged view of molecular ensembles in crystals. In the absence of rigid-body motions and lattice defects, B-factors are thought to accurately reflect the structural heterogeneity of such ensembles. In order to study the effects of averaging on B-factors, we employ molecular dynamics simulations to controllably manipulate microscopic heterogeneity of a crystal containing 216 copies of villin headpiece. Using average structure factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
119
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(123 citation statements)
references
References 74 publications
4
119
0
Order By: Relevance
“…Because the latter codependence of activity could be rationalized by a dynamic functional role of these residues, we turned to the highresolution X-ray data (13,15) deposited in the Protein Data Bank (PDB; www.rcsb.org) (16) to provide evidence of their dynamic motion within the crystal structure. Several recent studies have shown that the information present in such data is often underestimated and that it is possible to refine multiple conformations of residues simultaneously, each with individually refined occupancy and B factors, without overfitting the data (17)(18)(19)(20)(21)(22). By such sampling of low-level electron density, discrete, "hidden" conformations are revealed, facilitating a more quantitative representation of dynamic…”
mentioning
confidence: 99%
“…Because the latter codependence of activity could be rationalized by a dynamic functional role of these residues, we turned to the highresolution X-ray data (13,15) deposited in the Protein Data Bank (PDB; www.rcsb.org) (16) to provide evidence of their dynamic motion within the crystal structure. Several recent studies have shown that the information present in such data is often underestimated and that it is possible to refine multiple conformations of residues simultaneously, each with individually refined occupancy and B factors, without overfitting the data (17)(18)(19)(20)(21)(22). By such sampling of low-level electron density, discrete, "hidden" conformations are revealed, facilitating a more quantitative representation of dynamic…”
mentioning
confidence: 99%
“…Many methods have emerged for using Bragg data to model conformational diversity in protein crystals (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The development of these methods has been important as conformational diversity can lead to inaccuracies in protein structure models (9,(18)(19)(20). A key limitation of using the Bragg data, however, is that different models of conformational diversity can yield the same mean electron density.…”
mentioning
confidence: 99%
“…It has been suggested that the extent of atomic motions is significantly underestimated by B-factor refinement [59], especially when distinct alternate conformations are sampled [60]. It becomes increasingly clear that even with high-resolution X-ray diffraction data (and even more so with low-resolution data), a single model might often not be sufficient to describe the experimental data, due to conformational heterogeneity and dynamics [61,62 ,63,64].…”
Section: Uncertainty Error and Dynamicsmentioning
confidence: 99%